2011
DOI: 10.1109/lawp.2011.2163609
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Rain Attenuation From Experimental Drop Size Distributions

Abstract: Detailed measurements of the rain phenomena can be obtained from modern equipment that provides experimental drop size distributions (DSDs), which can be used to analyze the effects of past rain events or to predict their influence on colocated radio links. In this letter, the use of experimental DSDs to predict rain effects on millimeter-wave propagation is discussed from a practical point of view, taking advantage of the availability of measurements from various instruments. The derived results show that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…As clarified in the last paragraph, rain characteristics in tropical regions may cause a real obstacle against the propagation of mm‐wave signals. Raindrops may interact with the propagated signal by imposing various physical effects such as scattering, reflection, absorption, depolarization, and rain temperature . Each raindrop will act as an obstacle facing the microwave signal, particularly, when raindrop size is comparable to the signal wavelength as depicted in Figure .…”
Section: Precipitation Impact On Mm‐wavementioning
confidence: 99%
“…As clarified in the last paragraph, rain characteristics in tropical regions may cause a real obstacle against the propagation of mm‐wave signals. Raindrops may interact with the propagated signal by imposing various physical effects such as scattering, reflection, absorption, depolarization, and rain temperature . Each raindrop will act as an obstacle facing the microwave signal, particularly, when raindrop size is comparable to the signal wavelength as depicted in Figure .…”
Section: Precipitation Impact On Mm‐wavementioning
confidence: 99%
“…Fig. 14 shows the predicted rain attenuation in dB/km using (6) and (9) for the three rain events applying the ITU-R P. 838-3 model and the DSD model with Mie scattering, respectively. For lower rain rates, the ITU model predicted attenuation is slightly larger than the DSD model, while for higher rain rates, the ITU model predicted attenuation is smaller than the DSD model.…”
Section: ) Dsd Model and Rain Scattering Propertiesmentioning
confidence: 99%
“…In [8], rain attenuation was measured at 20.2 GHz and 30.5 GHz based on a GSAT-14 satellite in a tropical region. In [9], rain attenuation was measured based on a 19.7 GHz satellite link and a 38 GHz terrestrial link. The results for 75 GHz and 85 GHz terrestrial links are reported in [10].…”
Section: Introductionmentioning
confidence: 99%
“…The effect increases further with higher frequency bands, rainfall rates, longer path length, and larger raindrop sizes. This attenuation, caused by rain, reduces the reliability, systems availability, reception of signal‐to‐interference‐plus‐noise ratio (SINR), and overall performance of the communications link . As a result, rain attenuation is a real and concerning issue facing the implementation of mm‐waves, especially in tropical regions with consistent heavy rainfall such as Malaysia.…”
Section: The Effect Of Rain On the Propagation Of Mm‐wavesmentioning
confidence: 99%